Determinants of Incidence of Chronic Energy Deficiency (SEZ) in Pregnant Women at the Central City Health Center - Citra Nefadillah Pratiwi Djafar; Laksmyn Kadir; Suardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Chronic Energy Deficiency (KEK) in pregnant women is still a public health problem that can increase the risk of anemia and low birth weight babies (BBLR). The incidence of KEK is influenced by various factors such as healthy nutritional behavior, number of family members, Antenatal Care (ANC) visits, husband support, compliance with Fe consumption and maternal age. This study aims to determine the determinants of the incidence of Chronic Energy Deficiency (SEZ) in pregnant women at the Central City Health Center. This study uses an observational analytical method with a cross-sectional design. The research was carried out from January 29 to February 19, 2026 with a sample of 43 respondents. Sampling technique uses accidental sampling method. The research instrument uses a questionnaire that has been tested for Validity and Reliability. Data analysis was carried out univariate and bivariate using the Chi-square test with the value of . The results of the study showed that as many as 39.5% of respondents experienced SEZ incidents and 60.5% did not experience SEZs. There was no association between the number of family members (=0.850), Antenatal Care (ANC) visits (=0.281), and maternal age (=0.151) with the incidence of SEZs. However, there was a relationship between healthy nutritional behavior (=0.000), husband support (=0.000), and compliance with Fe consumption (=0.001) with the incidence of KEK in pregnant women. The conclusion of the study showed that healthy nutritional behavior, husband support, and compliance with Fe consumption were related to the incidence of KEK in pregnant women, while the number of family members, ANC visits, and maternal age were not related to the incidence of KEK in pregnant women at the Central city health center. It is recommended that health workers improve nutrition education, monitor Fe consumption, and involve families, especially husbands, in efforts to prevent KEK in pregnant women.